Controle social (democrático?) e previdência social: uma relação possível no contexto brasileiro? - Silva, Marcia Ribeiro (2020)
Social Security emerges in the Brazilian trajectory as one of the pillars of social protection for the working class, despite the requirements of capitalism. In the contemporary world, however, it faces successive challenges arising from the neoliberal offensive to deconstruct social policies, which aim to overthrow the bases of public welfare, for the benefit of financial or rentier capital, by transferring the public fund in the context of the State's counter-reform. In this sense, it should be noted that the decisions regarding Brazilian economic policy have implications for social (democratic) social control and, in particular, for the competences exercised within the scope of social security councils. Therefore, in this dissertation, the general objective was to analyze the exercise of social control (democratic) in the National Social Security Council (NSSC), with emphasis on the period 2011-2016, indicating progress and challenges. As specific objectives, the following were established: a) to contextualize the historical construction of the Brazilian social security policy; b) identify, classify and analyze the content of NSSC minutes, with an emphasis on composition, topics under debate and competences; and c) examine the decision-making process of NSSC, characterized by the stages of proposition, debate, referral and decision, through the minutes published in the period 2011-2016, in order to indicate progress and challenges for the exercise of (democratic) social control. This study is distinguished as an exploratory-descriptive research, of documentary type and qualitative and quantitative approach. Dialectical historical materialism was the method used to compare the data obtained with the theoretical framework. The documentary research presents as a primary source the documentary analysis of the ordinary and extraordinary minutes of NSSC, prepared in the period 2011-2016, and the legal-institutional social security frameworks, which are preponderant for the construction, consolidation and exercise of competences by the aforementioned collegiate. For the organization and treatment of the collected material, the technique of content analysis was used, consisting of the stages of pre-analysis, exploration of the material and treatment of the results. The main results of the research revealed: a) the distancing of NSSC from the premise of popular participation and from the principle of political and administrative decentralization consolidated in the Federal Constitution of 1988; b) the tendency to exclude direct participation by civil society in the formulation, monitoring and evaluation of social security policy; and c) the maintenance of corporate and centralizing practices within the scope of the Executive Branch. It is concluded that Social Security, despite the advances in the exercise of social (democratic) control, has for challenges, within the framework of capitalist society, the effectiveness of the participation of the working class / subordinate within the scope of the NSSC.